FAKTOR-FAKTOR KEINGINAN PINDAH AGEN REAL ESTATE WINSTON DI SURABAYA (Jurnal Manajemen dan Kewirausahaan, 2014)
This research was conducted to determine the factors that affect the desire to move Winston real estate agent in Surabaya. The population in this study amounted to 149 people. The sample of this research used the method of sampling of incidental to the level of a 10% error. Sample of this research as many as 113 people. This research used a quantitative approach. The technique of collecting data used questionnaires completed by respondents. Methods of data analysis that was used by the analysis of the factor. Analysis of the factor was ordained by using program Statistical Package for the Social Science (SPSS) which consists of two stages: a descriptive analysis and extraction. The results of this research show that the factors which affect the desire to move were composed of factors of individual and organizational factors. Individual factors which are more dominant than the system factors of the organization.